Converting the “union curious”? Rights-based, pro-worker arguments and Republican support for expanding collective bargaining: The case of the Illinois Workers’ Rights Amendment - Nicholas W. Waterbury; Magic M. Wade; Alan J. Simmons (PLoS ONE, 2026)
In 2022 Illinois voters were faced with a ballot measure asking them whether they supported adding a Workers’ Rights Amendment (WRA) to the state constitution. Despite countervailing forces that might have made passage difficult, the amendment passed. We explore whether support for collective bargaining rights and union protections followed a predictably partisan pattern in Illinois, or whether support for the amendment was shaped by arguments, endorsements, or other voter demographics. Fielding a survey experiment with a representative sample of 1,000 Illinois voters, we find that Democrats were more likely to support the WRA in general, but that Republicans were more likely to support it following exposure to rights-based arguments emphasizing better pay, benefits, and conditions for workers. We also find that Democrats were more likely to support it following exposure to public sector union endorsements, but that private sector endorsements did not sway Republicans. More broadly, these findings suggest future opportunities to influence potentially skeptical audiences when it comes to ballot measures related to the labor movement.